EVALUACIÓN DE GANANCIAS DE PESO EN DOS LÍNEAS DE HEMBRAS BROILERS EN CONDICIONES AMBIENTALES DEL TRÓPICO, EN EL CANTÓN BABAHOYO. - ESTÉVEZ JARAMILLO, LINDA MARICRUZ (2018)
Summary 400 female Broilers were used; 200 of the line Ross 308 and 200 of the line Cobb 500 of a day of age. The breeding was carried out in two buildings with an uncontrolled environment with the objective of evaluating the behavior of weekly weights indicators, average weekly gain, average daily gain and weekly average accumulated gain in tropical conditions. The study was carried out with a factorial design, the factors were the ship, the type of feeding (flour or pellets) and the lines, with 4 repetitions of each combination of the factors. The experimental unit consisted of 25 female animals with a density of 12 chickens / m². The barracks were randomly distributed in two ships with two repetitions of each combination of factors. Data were processed in the SPSS statistical package (version 23), simple variance analyzes with interactions and analysis of covariance were performed. The average weekly gain and weekly average accumulated gain presents allowable values for farms in the tropics with estimated averages ranging from 109.4 g to 145.5 g for week 1 and 376.9 g to 487.4 g in week 6 for the average weekly gain. The weekly cumulative average gain with ranges from 110.1 g to 135.5 g for the first week and 2035.4 g to 2086.1 g for the sixth week. The values of the three variables are slightly lower than those set by the productive performance manuals of the lines under study. Keywords: Broilers, line, pellets, flour, half and earnings